Determinasi Motivasi, Pelatihan, dan Gaya Kepemimpinan terhadap Kinerja Karyawan di Sektor Manufaktur: Studi Kasus PT Adi Satria Abadi Yogyakarta - Krishananta Wijaya; Dwi Utami Puterisari (Journal of Economics, Management, and Accounting, 2025)
Digital transformation has changed the landscape of the global manufacturing industry, including  This study investigates the determinants of motivation, training, and leadership style on employee performance in the leather manufacturing sector, with a case study at PT Adi Satria Abadi Yogyakarta. Using a quantitative approach with 75 randomly selected respondents, data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that leadership style has the most dominant influence on employee performance (β = 0.537, t = 8.421), followed by motivation (β = 0.277, t = 3.192), while training has a positive but insignificant effect (β = 0.135, t = 1.512). The R² value of 0.728 indicates that 72.8% of performance variation is explained by the three independent variables. These findings emphasize that transformational leadership and intrinsic motivation are critical to enhancing performance, while training effectiveness depends on contextual relevance. The study contributes theoretically to human resource management by affirming the strategic synergy among leadership, motivation, and competence development, and provides practical recommendations for strengthening adaptive management systems in manufacturing industries.